Numerical simulation of heat and mass transfer of a wall containing micro-encapsulated phase change concrete (PCC) - Lajimi, Nour; Ben Taher, Nour; Boukadida, Noureddine (Frontiers in Environmental Science, 2023)
In the building sector, it is essential to know and master the behavior of the premises (through the mastery of the phenomena of heat and water transfers in the first place) before thinking of equipping them with energy systems (air conditioners, heat pumps, heat exchanger, etc.). The thermal insulation of the ceiling seems to be effective given the importance of solar radiation to which it is exposed in summer and its significant contribution to energy loss during winter. The objective of this work is to study the heat and mass transfer through a ceiling wall containing micro-encapsulated PCM (phase change Materials) under realistic climatic conditions based on meteorological data in Tunisia. This work relates to a numerical study based on software (DIGITAL Visual FORTRAN95) to predict the effect of the integration of a layer of PCM on the thermal behavior, mass and on the thermal comfort of the occupant as well as on the energy consumption for the summer and winter periods.